The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1073/pnas.1611098113
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous yet stable Vδ2 (+) T-cell profiles define distinct cytotoxic effector potentials in healthy human individuals

Abstract: Human γδ T cells display potent responses to pathogens and malignancies. Of particular interest are those expressing a γδ T-cell receptor (TCR) incorporating TCRδ-chain variable-region-2 [Vδ2(+)], which are activated by pathogen-derived phosphoantigens (pAgs), or host-derived pAgs that accumulate in transformed cells or in cells exposed to aminobisphosphonates. Once activated, Vδ2(+) T cells exhibit multiple effector functions that have made them attractive candidates for immunotherapy. Despite this, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 42 publications
23
109
0
Order By: Relevance
“…Unfortunately, due to the difficulty in recruiting women (31), our study only included men. However, we acknowledge that gender differences may exist, given controversial findings in previous work according to γδ T cell frequencies (32)(33)(34), that may potentially translate into functional differences. Current work is focused towards this end.…”
Section: Figure 5 Vδ2 Cells Degranulate In the Presence Of Autologoumentioning
confidence: 82%
“…Unfortunately, due to the difficulty in recruiting women (31), our study only included men. However, we acknowledge that gender differences may exist, given controversial findings in previous work according to γδ T cell frequencies (32)(33)(34), that may potentially translate into functional differences. Current work is focused towards this end.…”
Section: Figure 5 Vδ2 Cells Degranulate In the Presence Of Autologoumentioning
confidence: 82%
“…In contrast, γδ T cells within the CB lacked gzm A, B and K expression, with only gzm M being moderately expressed (̃15%, n = 3; Figure a). As Vδ2 + and Vδ2 − TCRγδ + subsets have previously shown to have differential functional capacities and phenotypic profiles, we further segregated gzm and perforin staining into Vδ2 + and Vδ2 − TCRγδ + subsets. Indeed, our frequency analyses of individual single cytotoxic molecules in healthy adults verified the previous findings and showed that the Vδ2 + T cells had significantly higher frequency of all molecules with the exception of Gzm B, as compared to Vδ2 − TCRγδ + cells (Figure b; P = Gzm A, K, M = 0.008, perforin = 0.023).…”
Section: Resultsmentioning
confidence: 99%
“…Studies analyzing the immune cell repertoire in healthy adults found that PD-1 expression is higher in Vδ1+, compared to Vδ2 + T-cells 15 but similar within several functionally distinctive subsets of Vδ2 T-cells. 16 Others reported differences in PD-1 expression depending on CD27 and CD45RA status with preferential expression in the effector-memory subsets. 9 We found a mean of 40% PD-1(+) on γδ T-cells in unstimulated human peripheral blood (Figure 1(a)) while three earlier studies found lower fractions of PD-1(+) cells (< 10%) 7,10,15 and others reported higher values.…”
Section: Expression Of Pd-1 By γδ T-cells In Health and Diseasementioning
confidence: 99%